Management for productivity - Schermerhorn, John R (Wiley, 1986)
Includes bibliographical references and indexes.; Prepares managers for the 21st century workplace while continuing to focus on achieving productivity through good management. Contains many ''real-world'' examples, showing the practice of management in organizations of all types and sizes. Covers history of management thought, current applications of theory, managerial decision making and problem solving, career planning and development, new directions in labor-management relations, operations and service management.